Groundwater Depth Affects Phosphorus But Not Carbon and Nitrogen Concentrations of a Desert Phreatophyte in Northwest China - Zhang, Bo; Gao, Xiaopeng; Li, Lei; Lu, Yan; Shareef, Muhammad; Huang, Caibian; Liu, Guojun; Gui, Dongwei; Zeng, Fanjiang (Frontiers in Plant Science, 2018)
Ecological stoichiometry is an important aspect in the analysis of the changes in ecological system composition, structure, and function and understanding of plant adaptation in habitats. Leaf carbon (C), nitrogen (N), and phosphorus (P) concentrations in desert phreatophytes can be affected by different depths of groundwater through its effect on the adsorption and utilization of nutrient and plant biomass. We examined the biomass, soil organic C, available (mineral) N, and available P, and leaf C, N, and P concentrations of Alhagi sparsifolia grown at varying groundwater depths of 2.5, 4.5, and 11.0 m in 2015 and 2016 growing seasons in a desert-oasis ecotone in northwest China. The biomass of A. sparsifolia and the C, N, and P concentrations in soil and A. sparsifolia showed different responses to various groundwater depths. The leaf P concentration of A. sparsifolia was lower at 4.5 m than at 2.5 and 11.0 m likely because of a biomass dilution effect. By contrast, leaf C and N concentrations were generally unaffected by groundwater depth, thereby confirming that C and N accumulations in A. sparsifolia were predominantly determined by C fixation through the photosynthesis and biological fixation of atmospheric N2, respectively. Soil C, N, and P concentrations at 4.5 m were significantly lower than those at 11.0 m. Leaf P concentration was significantly and positively correlated with soil N concentration at all of the groundwater depths. The C:N and C:P mass ratios of A. sparsifolia at 4.5 m were higher than those at the other groundwater depths, suggesting a defensive life history strategy. Conversely, A. sparsifolia likely adopted a competitive strategy at 2.5 and 11.0 m as indicated by the low C:N and C:P mass ratios. To our knowledge, this study is the first to elucidate the variation in the C, N, and P stoichiometry of a desert phreatophyte at different groundwater depths in an arid ecosystem.